Understanding factors associated with children achieving recommended amount of MVPA on weekdays and weekend days - Button, Brenton L.G. (Prev Med Rep, 2020)
Low levels of moderate-to-vigorous physical activity (MVPA) are consistently reported for children from industrialized countries. Perennially inadequate levels of MVPA have been linked to increased chronic disease risks. Very few studies have compared physical activity levels among children from geographically diverse places, and how they differ on weekdays versus weekends. The purpose of this research is to examine the factors that influence whether children achieve 60 min of MVPA on weekdays compared to weekend days. Data were analyzed on children (n = 532) aged 8–14 years from communities in Southern and Northern Ontario, Canada that participated in the study between 2009 and 2016. Children’s MVPA was measured using an Actical accelerometer, environmental features measured with a geographic information system, and demographic data came from child/parent surveys. Variables were selected using a least absolute shrinkage and selection operator. The variables were entered into logistic regression models to assess the relationship between children meeting the MVPA guidelines. During the week, boys were more active than girls (OR = 4.652 p < 0.001) and as age increased children were less likely to reach the MVPA guidelines (OR = 0.758 p = 0.013). On weekends boys were still more likely to meet the guidelines (OR = 1.683 p = 0.014) and children living in rural Northern Ontario were more likely to reach the MVPA guidelines compared to all groups in Southern Ontario. The findings indicate that different variables influence whether children meet the MVPA guidelines on weekdays compared to weekends. Comparing weekdays and weekends provides more useful information for creating effective MVPA interventions.